Colostrum-Derived Melatonin Plus PEG Microspheres Modulate the Oxidative Metabolism of Human Colostrum Phagocytes - Caroline G. Silva; Viviane F. Luz; Victor L. Nunes; Ana B. M. Verzoto; Aron C. de M. Cotrim; Wagner B. dos Santos; Eduardo L. França; Adenilda C. Honorio-França (Metabolites)
Background/Objectives: Exogenous melatonin adsorbed onto PEG microspheres can modulate the functional activity of phagocytes in colostrum, but no data are available on the activity of melatonin found in colostrum. Therefore, the objective of this study was to extract melatonin from human colostrum, develop and characterize PEG microspheres with the extracted melatonin adsorbed onto them, and evaluate the effects of this system on the oxidative metabolism of colostrum phagocytes. Methods: Thirty colostrum samples were collected; ten were used for melatonin extraction, while twenty were used to obtain phagocytes. Melatonin was extracted from the colostrum supernatant through affinity chromatography and quantified by ELISA. The polyethylene glycol microspheres produced were analyzed using fluorescence microscopy and flow cytometry. Oxidative metabolism was assessed by measuring the release of the superoxide anion and superoxide enzymes. A control was conducted using commercial melatonin. Results: The fluorescence microscopy and flow cytometry analyses demonstrated that PEG microspheres can adsorb melatonin. There was an increase in superoxide release in phagocytes incubated with colostrum-derived or synthetic melatonin. When exposed to bacteria, colostrum phagocytes treated with colostrum melatonin adsorbed to PEG microspheres exhibited increased superoxide, accompanied by a decrease in the release of superoxide dismutase (SOD) and a lower SOD-to-superoxide ratio. In contrast, synthetic melatonin reduced the release of superoxide and increased the release of the enzyme and the SOD-to-superoxide ratio. Conclusions: These data highlight the importance of melatonin on cellular metabolism and suggest that colostrum-derived melatonin may be a more effective option for controlling oxidative metabolism, particularly during infectious processes.